Influence of Natural Hypolipidemic Compounds on Formation of Pseudomonas biofilms - T. O. Puzhevskaya; M. V. Bibikova; N. E. Grammatikova; N. A. Mikhailova; A. V. Katlinsky (Антибиотики и Химиотерапия, 2020)
Natural compounds showing considerable inhibitory effect on formation of biofilms by P.aeruginosa were selected. Synergism of the compounds with gentamicin with respect to both the inhibition of the biofilm formation and the gentamicin antibacterial effect was stated.